Single mothers figuring out their future family life - understanding family development after separation and divorce drawing upon the concept of configuration - Claudia Equit; Matthias Euteneuer; Uwe Uhlendorff (Social Work & Society, 2022)
In this paper, we will discuss the results of a qualitative longitudinal study on single parent families against the background of the concept of configuration as developed by Norbert Elias. We will examine the extent to which the conceptual and analytical possibilities of this approach help us to understand the dynamics of family development after divorce or separation. Our qualitative study is focused on the question of how single mothers reflect upon, develop, and change their family configurations after separation and divorce. Based on semi-structured interviews, we explore four issues from the point of view of single mothers: (1) in which kind of family configuration are single mothers living? (2) What kind of family configuration do they want to live in future? (3) Which patterns of orientation underlie their reflection processes and serve as key drivers for the intended transformations or perpetuation of their family configuration? Overall, we will argue that the concept of relative autonomy for the people involved in (family) configurations is extremely helpful for both the academic understanding of family development and the practical social work with families.